'There is more flexibility to meet my needs': Educational experiences of autistic young people in Mainstream and Alternative Education Provision. Issue 1 (25th March 2019) - Goodall, Craig
Abstract: Through a qualitative rights informed study, using semi‐structured interviews and a range of participatory approaches, seven autistic teenage boys in Northern Ireland discuss their educational experiences in mainstream school and within an Alternative Education Provision (AEP). Their experiences and advice demonstrate that the relational aspects of education, the understanding and flexibility afforded in the AEP, within a less socially intense, more predictable and less overwhelming environment and with other young people who had 'similar' educational experiences, better supported their needs. In short, for most of them, an accessible education and the feeling of inclusion was found within the AEP as opposed to the mainstream school they attended previously.